Active surveillance of prostate cancer: a questionnaire survey of urologists, clinical oncologists and urology nurse specialists across three cancer networks in the United Kingdom - Philippou, Yiannis (BMC Urol, 2015)
BACKGROUND: Active surveillance is considered a mainstream strategy in the management of patients with low-risk prostate cancer. A mission-critical step in implementing a robust active surveillance program and plan its resource and service requirements, is to gauge its current practice across the United Kingdom. Furthermore it is imperative to determine the existing practices in the context of the recommendations suggested by the recent National Institute for Health and Clinical Excellence guidance on active surveillance of prostate cancer. METHODS: An internet questionnaire was circulated to urologists, clinical oncologists and urology nurse specialists across three geographically distinct cancer networks. Twenty five questions across four domains were assessed. (i) hospital resources (staff and clinical areas) utilised for active surveillance (ii) enrolment criteria (iii) follow up (iv) criteria that trigger conversion to active treatment. RESULTS: We received 35 responses, 20 of which were from urologists. The survey data suggests that there is marked heterogeneity in enrolment criteria with patients having features of intermediate-risk prostate cancer often recruited into Active Surveillance programs. Only 60 % of our respondents use multiparametric MRI routinely to assess patient suitability for active surveillance. In addition, marked variation exists in how patients are followed up with regard to PSA testing intervals and timing of repeat biopsies. Only 40 % undertake a repeat biopsy at 12 months. Tumour upgrading on repeat biopsy, an increase in tumour volume or percentage of core biopsies involved would prompt a recommendation for treatment amongst most survey respondents. In addition allocation of resources and services for active surveillance is poor. Currently there are no dedicated active surveillance clinics, which are well-structured, -resourced and -supported for regular patient counselling and follow up. CONCLUSION: This variability in enrolment criteria and follow up is also demonstrated in international and national series of active surveillance. Resources are not currently in place across the UK to support an active surveillance program and a national discussion and debate to plan resources is much required so that it can become a mainstream therapeutic strategy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12894-015-0049-y) contains supplementary material, which is available to authorized users.